Effect of social isolation due to COVID-19 on BMI in school children - Azrak, María Ángeles (2021)
Introduction: Preventive and compulsory social isolation (ASPO) and the resulting closure of schools and suspension of sports practice reduced physical activity; this could affect children causing changes in lifestyle and consequently body mass index (BMI).Objective: to evaluate the effect of ASPO (March-October 2020) on the changes in BMI and lifestyle in children aged 6 to 9 years old in La Plata, Buenos Aires.Methods: Children who underwent their health checks at La Plata Children Hospital-IDIP Health Observatory in the 4 months prior to the ASPO were summoned in November 2020 to assess anthropometric variables (weight, height, BMI expressed as z-score) and lifestyle (diet, physical activity and sleep). A historical control group (GH) was established with anthropometric data from older children who did not experience ASPO between 6 and 9 years old.Results: 140 children were evaluated. Body weight increased during the ASPO (zBMI/age: 0.47 vs GH=0.04; p<0.001). Children reported less physical activity (52.3%), increased screen time (75%) and sleeping more hours (46.6%) than before the ASPO. Children with pre-existing overweight/obesity gained more weight (6.25 vs 3.0 kg in normal weight children; p<0.001), associated with reduced physical activity (2 h/day vs 3 h/day in normal weight children; p<0.001) and not to changes in diet.Conclusion: ASPO affected lifestyle and weight gain in children; those with pre-existing overweight/obesity were more affected. Our findings can guide efforts to preserve and promote child well-being during lockdown, helping governments to decide the confinement rules to apply to children, especially regarding school closing.